A emergência dos "agricultores familiares" como sujeitos de direitos na trajetória do sindicalismo rural brasileiro - Lazzaretti Picolotto, Everton (2009)
The process of the family farmers' recognition as individuals with rights demonstrates having their first roots, in spite of being recent, if compared to the history of the Brazilian rural syndicalism, still in the constitution of the labor-syndical legislation in 1930. Therefore, seeking to explore that process the present paper has as objective to analyze the family farmers' emergence as individuals of rights in the contemporary Brazilian society, analyzing the processes of formation of the rural syndicalism and the expansion of the labor law for the rural workers as a form of accomplishment of a "regulated citizenship" until the decade of 1970; the urge to the official syndicalism, the structuring of a "new syndicalism" and the new social actors' appearance in the field, which made possible the enlargement of the citizenship spaces in the period of re-democratization in Brazil; the "crisis" of the new syndicalism, the creation of new syndical structures "apart" of the official structure (syndicalism of the family agriculture) and the emergency of the "family farmers" as subject of rights in the recent period.